Psicoeducational intervention with men who exert violence - HEV: A multidimensional model - Deza Villanueva, Sabina (2009)
There are programs for men who exert violence in couple relations with women, in the Anglo-Saxon and Scandinavian world (United States, Canada, Sweden, Australia) since more than thirty years ago and eighteen years ago in the Hispanic world ( Argentina, Mexico). In the present research, we propose a multidimensional model with a gender perspective which includes cognitive, behavioral, emotional and historical dimensions of violent behavior, and incorporates different theoretical references. This causes the coordination of this problem -men who exert violence- and the possibilities of an intervention that pay completely attention to those components. This model supports with a gender perspective the importance of working psychoeducational strategies which permit that HEV assume the responsibility about the violence, critical consciousness about the use of violence and the place it has in himself and in the relation with women; just as the consequences of that behavior affects the partner and family. This model makes evident a denied and common woman, raising her to individual status.